An Innovative Approach of N-Soft Quotient Topological Space - G. Kabin Antony; M. Lellis Thivagar; B. Tamilarasan; Mequanint Birhan (Advances in Materials Science and Engineering)
In the many approaches to soft set theory, the theory of N-soft topological space is a key component of studying topology. The notions of soft mapping in N-soft topological space as well as a novel notion of N-soft continuous mapping, N-soft quotient mapping, and N-soft quotient topology are discussed in this article. We also look at some of its traits and outcomes. It will give the foundation for real-world applications in this subject.